Assessment of burnout among pharmacy faculty in the Kingdom of Saudi Arabia - Raniah Aljadeed; Rana Aljadeed; Ghadah Assiri; Nora A. Kalagi (BMC Medical Education)
Abstract Background Burnout is a condition closely linked to deteriorating mental health and diminished work performance. There is a lack of research on burnout among pharmacy faculty in the Kingdom of Saudi Arabia. This study aims to assess the burnout rate among pharmacy faculty members in the Kingdom of Saudi Arabia and to identify predictive factors that contribute to or precipitate the onset of burnout. Methods A cross-sectional, anonymous electronic survey was distributed to all pharmacy faculty members in the Kingdom of Saudi Arabia. The survey included the Maslach Burnout Inventory-Educators Survey, which measures three dimensions of burnout: emotional exhaustion, depersonalization, and personal accomplishment. Demographic data, Maslach Burnout Inventory-Educators scores, and potential predictors of burnout were collected and analyzed. Results A total of 246 pharmacists participated in this study. Among them, 30.4% reported experiencing emotional exhaustion, and a similar percentage scored low on the personal accomplishment subscale. Additionally, 10.9% of the sample exhibited high scores on the depersonalization subscale. The burnout rate was found to be influenced by several factors, including citizenship, the presence of children in the household, and faculty members’ academic rank. Conclusion Pharmacy faculty members at pharmacy colleges in the Kingdom of Saudi Arabia are experiencing significant burnout, particularly in the form of emotional exhaustion and low personal accomplishment scores. Key factors contributing to burnout include citizenship, the presence of children in the household, and academic rank.